Sex differences in neonatal outcomes following prenatal opioid exposure - Madurai, Nethra K.; Jantzie, Lauren L.; Yen, Elizabeth (Frontiers in Pediatrics, 2024)
The impact of the opioid epidemic on pregnant people and children is a growing public health crisis. Understanding how opioids affect the developing brain during pregnancy and postnatally remains a critical area of investigation. Biological sex plays a crucial role in all physiologic processes, with the potential for a significant impact on neonatal outcomes, including those infants with opioid exposure. Here, we aim to explore current literature on the effect of sex on neonatal outcomes following prenatal opioid exposure. Sex differences in adults with opioid use disorder have been well studied, including increased mortality among males and higher rates of psychiatric comorbidities and likelihood of relapse in females. However, such differences are not yet well understood in neonates. Emerging clinical data suggest sex-specific effects in infants with prenatal opioid exposure on the expression of genes related to feeding regulation and reward signaling pathways. Increased susceptibility to white matter injury has also been noted in female infants following prenatal opioid exposure. Understanding the impact of sex as a biological variable on neonatal outcomes following prenatal opioid exposure is paramount to improving the health and well-being of infants, children, and adults impacted by the opioid epidemic.